Multilayer proximity coupled rectangular patch antenna / Mohamad Fauzi Ahmad Tajuddin - Ahmad Tajuddin, Mohamad Fauzi (2010)
In this paper, a new invention of multilayer proximity coupled rectangular patch antenna operating at the frequency of 3.5GHz is presented. This frequency is applicable for WiMAX application. In designing antenna, there are four factors involved that need to be concentrate on which include dielectric constant cr of the substrate, thickness of the substrate, length and width of the feed line, and also the patch dimension calculation. The substrate used is RO 3003 for lower substrate while RT Duroid 5870 is used as the upper substrate. To analyze the performance of the antenna, CST software is used and the result of simulation determined by analyzing the return loss Sn , VSWR, bandwidth, and farfield. The results from electromagnetic simulation of the antenna are presented through this paper.